1993
DOI: 10.1128/jb.175.3.767-778.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inducible nickel and cobalt resistance determinant cnr from pMOL28 of Alcaligenes eutrophus CH34

Abstract: From pMOL28, one of the two heavy metal resistance plasmids of Alcaligenes eutrophus strain CH34, we cloned an EcoRI-PstI fragment into plasmid pVDZ'2. This hybrid plasmid conferred inducible nickel and cobalt resistance (cnr) in two distinct plasmid-freeA. eutrophus hosts, strains AE104 and H16. Resistances were not expressed in Escherichia coli. The nucleotide sequence of the 8.5-kb EcoRI-PstI fragment (8,528 bp) revealed seven open reading frames; two of these, cnrB and cnrA, were assigned with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
177
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(191 citation statements)
references
References 39 publications
6
177
0
1
Order By: Relevance
“…It has been suggested that SigX may play a similar role in B. subtifis (17). (12,(32)(33)(34) (14), and preliminary sequence similarities suggest that the E. coli 0.E operon also encodes a negative regulator (M.A.L., data not shown). Although the precise mechanism of negative regulation in these systems has not been established, in the case of CarQ the stoichiometry ofthe a factor and its negative regulator is critically important.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that SigX may play a similar role in B. subtifis (17). (12,(32)(33)(34) (14), and preliminary sequence similarities suggest that the E. coli 0.E operon also encodes a negative regulator (M.A.L., data not shown). Although the precise mechanism of negative regulation in these systems has not been established, in the case of CarQ the stoichiometry ofthe a factor and its negative regulator is critically important.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic determinants for Ni resistance have been first identified and characterized at the molecular level from Alcaligenes xylosoxidans 31A (known also as Ralstonia eutropha, then as Ralstonia metallidurans and now as Cupriavidus metallidurans 31A) and Alcaligenes eutrophus CH34 (now known as Cupriavidus metallidurans CH34) which were isolated from industrially contaminated sites (Mergeay et al 1978;Schmidt and Schlegel 1989). A. xylosoxidans 31A harbors two genetic determinants (ncc, nre) on plasmid pTOM9, while C. metallidurans CH34 contains one system only (cnr) (Liesegang et al 1993;Mergeay et al 2003;Nies 2000), but a large number of transporters and a regulatory apparatus are present also in its genome constituting an integrated (both plasmid-borne and chromosomal) system for resistance to metals (Mergeay et al 2003;von Rozycki and Nies 2008). In all these systems Ni resistance is due to an inducible efflux system, mediated by ATP binding cassette (ABC) transporters, that lower the intracellular Ni concentration by pumping out Ni cations from the cytoplasm (Mergeay et al 2003).…”
Section: Genes For Metal Resistance: Single Operons or Genome Adaptatmentioning
confidence: 99%
“…Resistance to Cd# + , Zn# + and Co# + has been shown to be located on a czc operon of the plasmid pMOL30 (240 kb), while Co# + combined with Ni# + resistance is located on the cnr operon of the plasmid pMOL28 (163 kb) (Liesegang et al, 1993 ;Mergeay et al, 1985 ;Nies et al, 1987 ;Siddiqui et al, 1989). Other plasmid-borne resistances to metals include resistance to copper (cop), lead ( pbr) and mercury (mer) on pMOL30 and resistance to chromate (chr) and mercury on pMOL28 (for a review see Mergeay, 2000).…”
Section: Introductionmentioning
confidence: 99%